2010
DOI: 10.1371/journal.pone.0015416
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Euchromatin on LAT and ICP4 Following Reactivation Are More Prevalent in an Efficiently Reactivating Strain of HSV-1

Abstract: BackgroundEpigenetic mechanisms, via post-translational histone modifications, have roles in the establishment and maintenance of latency of the HSV-1 genome in the sensory neurons. Considering that many post-translational histone marks are reversible in nature, epigenetic mechanisms may also play a critical role in the process of induced HSV-1 reactivation.Methodology/Principal FindingsThis study utilized the rabbit ocular model of HSV-1 infection and reactivation, induced by the transcorneal iontophoresis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…We and others have previously reported that transcriptionally permissive histone marks, specifically acetyl H3 K9, K14, and dimethyl H3 K4, accumulate on the repressed IE regions of HSV-1 by 2 to 4 h following the application of reactivation stimuli (1,13,31). This provides evidence that the distinct chromatin domains observed during latency are no longer intact at early times following reactivation stressors.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…We and others have previously reported that transcriptionally permissive histone marks, specifically acetyl H3 K9, K14, and dimethyl H3 K4, accumulate on the repressed IE regions of HSV-1 by 2 to 4 h following the application of reactivation stimuli (1,13,31). This provides evidence that the distinct chromatin domains observed during latency are no longer intact at early times following reactivation stressors.…”
mentioning
confidence: 52%
“…These key findings provide evidence that HSV-1 latency is established and maintained, at least in part, by complex epigenetic mechanisms that further poise the virus for reactivation. To support this, recent data show that the enrichments of euchromatic histone marks on the HSV-1 LAT and IE promoters change in response to reactivation stimuli in both rabbit and mouse models latently infected with wild-type HSV-1 (1,13,26,31,36). Specifically, histone marks on ICP0 and ICP4 rapidly and transiently become more euchromatic in nature, while the LAT region loses enrichment of euchromatic histone marks as LAT is degraded at early times in reactivation in the two different in vivo models (1,13,31).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Although the role and target of HSV-2 miR-H6 is unknown, and abrogation of its expression by insertion of a polyadenylation site directly upstream of the miRNA had no influence on acute viral infection or recurrence (26), it is possible that miR-H6 promoter sequences in exon 1 could be important for viral latency and recurrence phenotypes. During latency, these sequences (in HSV-1) are enriched for euchromatin marks (56)(57)(58)(59), likely playing a role in the expression of miR-H6 during latency and thus possibly also playing a role in the activity of the nearby LAT promoter.…”
Section: Discussionmentioning
confidence: 99%